PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN KERTAS KARTON BERGAMBAR TUTS ALAT MUSIK KEYBOARD UNTUK MEMFASILITASI BELAJAR SISWA KELAS X-1 DI SMAN 3 SURABAYA - Aries Afandri; Atiqoh; Ujang Rohman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to produce a product in the form of learning media to increase understanding and make it easier for students to play the keyboard and improve the overall quality of music learning at the school. This research uses a development method in the form of learning products, researchers use the Dick and Carey model development. This research was carried out at SMAN 3 Surabaya in class X. This is development research (Dick and Carey). The research objects were 18 students in class X-1. The product of this research is Cardboard Paper Learning Media with Keyboard Keys, with a percentage of feasibility Validation by Content Experts: The media is assessed as 100% appropriate based on 25 validation indicators which include aspects of introduction, content presentation, learning and evaluation. Design Expert: Media is assessed as 100% appropriate based on 18 validation indicators in aspects of appearance, suitability, content presentation, illustrations and media evaluation. Media Expert: Media is assessed as 100% appropriate based on 16 validation indicators related to media display, use and utilization. Trial on a large group of 18 students: The average indicator feasibility reached 99.12%, which proves the effectiveness of media in learning. The results of the researcher's findings are cardboard paper products with images of keyboard keys for learning. This product has high appeal, is easy to use, and really helps students in learning keyboard musical instruments, without the need to have an expensive physical keyboard. This media allows learning to be more interactive and fun.